Multi-Objective Optimization of Hobbing Process Parameters Based on Response Surface Method - Wang, Yazhou; Yin, Xiaohui (Engineering Transactions, 2025)
In hobbing machining, gear geometric accuracy is an important factor affecting gear working performance, which is determined by the interaction of different process parameters. To improve the geometric accuracy of hobbing surface and obtain the minimum geometric error, this paper adopts the response surface method (RSM) to study the effects of various technological parameters on the geometric accuracy, and explores the influence law of various factors on the geometric accuracy through the response surface diagram. The mathematical models of total profile deviation, total helix deviation, cumulative total deviation of tooth spacing and radial runout were established based on response surface method, and the reliability of the models was tested by variance analysis. Non-dominated sorting whale optimization algorithm (NSWOA) was used to solve the mathematical model, and Pareto solution set was obtained. Entropy weight-TOPSIS method was used to determine the optimal scheme after NSWOA algorithm optimization. After optimization, the total deviation of tooth profile is reduced by 8.04 %, the total deviation of helix is reduced by 9.17 %, the cumulative total deviation of tooth spacing is reduced by 3.88 %, and the radial runout is reduced by 7.45 %, which proves that the optimized scheme can improve the gear accuracy after hobbing machining, and provides a reference for the reasonable selection of gear hobbing process parameters.